Changes in olfactory bulb volume following lateralized olfactory training - Negoias, S.; Pietsch, K.; Hummel, T. (Brain imaging and behavior, 2017)
Repeated exposure to odors modifies olfactory function. Consequently, “olfactory training” plays a significant role in hyposmia treatment. In addition, numerous studies show that the olfactory bulb (OB) volume changes in disorders associated with olfactory dysfunction. Aim of this study was to investigate whether and how olfactory bulb volume changes in relation to lateralized olfactory training in healthy people. Over a period of 4 months, 97 healthy participants (63 females and 34 males, mean age: 23.74 ± 4.16 years, age range: 19–43 years) performed olfactory training by exposing the same nostril twice a day to 4 odors (lemon, rose, eucalyptus and cloves) while closing the other nostril. Before and after olfactory training, magnetic resonance imaging (MRI) scans were performed to measure OB volume. Furthermore, participants underwent lateralized odor threshold and odor identification testing using the “Sniffin‘ Sticks” test battery. OB volume increased significantly after olfactory training (11.3 % and 13.1 % respectively) for both trained and untrained nostril. No significant effects of sex, duration and frequency of training or age of the subjects were seen. Interestingly, PEA odor thresholds worsened after training, while olfactory identification remained unchanged.These data show for the first time in humans that olfactory training may involve top-down process, which ultimately lead to a bilateral increase in olfactory bulb volume.